Screening of ferulic acid related compounds as inhibitors of xanthine oxidase and cyclooxygenase-2 with anti-inflammatory activity - Nile,Shivraj Hariram (2016)
Abstract The ferulic and gallic acid related compounds from natural origin were studied against xanthine oxidase and cyclooxygenase-2 along with their anti-inflammatory activity. The compounds gallic acid, ferulic acid, caffeic acid and p-coumaric acid revealed promising anti-inflammatory activity (30–40% TNF-α and 60–75% IL-6 inhibitory activity at 10 µM). Bioavailability of compounds were checked by in vitro cytotoxicity using CCK-8 cell lines and confirmed to be nontoxic, but found toxic at higher concentration (50 µM). Gallic, ferulic, caffeic acid was demonstrated potential dual inhibition toward xanthine oxidase and cyclooxygenase-2 as calculated by IC50: 68, 70.2, and 65 µg/ml (xanthine oxidase) and 68.5, 65.2, and 62.5 µg/ml (cyclooxygenase-2), respectively. The structure activity relationship and in silico drug relevant properties (HBD, HBA, PSA, c Log P, ionization potential, molecular weight, EHOMO and ELUMO) further confirmed that the compounds were potential candidates for future drug discovery study, which was expected for further rational drug design against xanthine oxidase and cyclooxygenase.